(untitled) (Journal of Computational Mathematics, 2024)
Convergence of modified truncated Euler-Maruyama (MTEM) method for stochastic differential equations (SDEs) with (1/2 + α)-Hölder continuous diffusion coefficients are investigated in this paper. We prove that the MTEM method for SDE converges to the exact solution in L^q sense under given conditions. Two examples are provided to support our conclusions.